1987
DOI: 10.1200/jco.1987.5.9.1430
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD2 specific monoclonal antibody 3F8: a phase I study in patients with neuroblastoma and malignant melanoma.

Abstract: The murine IgG3 monoclonal antibody (MoAb) 3F8, specific for the ganglioside GD2, activates human complement, is active in antibody-dependent cell-mediated cytotoxicity (ADCC), and can target specifically to human neuroblastoma in patients with metastatic disease. In a phase I study, 3F8 was administered intravenously (IV) to 17 patients with metastatic GD2 positive neuroblastoma or malignant melanoma at doses of 5, 20, 50, and 100 mg/m2. Serum 3F8 levels achieved were proportional to the dose of 3F8 infused. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
208
0
6

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(214 citation statements)
references
References 13 publications
0
208
0
6
Order By: Relevance
“…In this regard, a previous study involving genetically-modified ICs such that FcR-binding capability was eliminated showed that IC-mediated antitumor effects could be obtained without FcR-binding [11]. MAb therapy has been used effectively in clinical trials as single agents, including the anti-GD 2 Ab 3F8 and precursors to the hu14.18-IL2 IC including the 14.G2a murine mAb and ch14.18 chimeric mAb [4][5]14,34]. The IL2 component of the IC augments the effects of mAb, and has been shown to increase the number and activation state of NK cells, as well as to stimulate tumor cell killing by antigen-specific T-cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a previous study involving genetically-modified ICs such that FcR-binding capability was eliminated showed that IC-mediated antitumor effects could be obtained without FcR-binding [11]. MAb therapy has been used effectively in clinical trials as single agents, including the anti-GD 2 Ab 3F8 and precursors to the hu14.18-IL2 IC including the 14.G2a murine mAb and ch14.18 chimeric mAb [4][5]14,34]. The IL2 component of the IC augments the effects of mAb, and has been shown to increase the number and activation state of NK cells, as well as to stimulate tumor cell killing by antigen-specific T-cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GD2 Abs are known to induce significantly painful side effects (25)(26)(27), with occasional reports of cranial or peripheral neuropathy. Anti-GD1a Abs preferentially immunostained motor fibers thought to cause motor neuropathies such as acute motor axonal neuropathy (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Fc-fragment of the murine antibody may not elicit ADCC or CDC as effectively as the Fc portion of a human antibody, as described above [45,46,47,48,49].…”
Section: Gd2 and Anti-gd2 Antibody Immunotherapymentioning
confidence: 99%